2013
DOI: 10.1016/j.bmc.2013.04.083
|View full text |Cite
|
Sign up to set email alerts
|

Recent syntheses of PI3K/Akt/mTOR signaling pathway inhibitors

Abstract: This review focuses on the syntheses of PI3K/Akt/mTOR inhibitors that have been reported outside of the patent literature in the last 5 years but is largely centered on synthetic work reported in 2011 and 2012. While focused on syntheses of inhibitors, some information on in vitro and in vivo testing of compounds is also included. Many of these reported compounds are reversible, competitive adenosine triphosphate (ATP) binding inhibitors, so given the structural similarities of many of these compounds to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 114 publications
(106 reference statements)
0
33
0
Order By: Relevance
“…Compound 13 ( Figure 6) was recorded as mTOR inhibitor selective over PI3K and inhibited downstream substrate Pakt of mTOR kinase up to 83% exhibiting dose-dependent inhibition [37]. This compound inhibited 18 cancer cell-lines' proliferation (IC 50 <1 μM) in tissue culture experiments, HGF-stimulated Akt phosphorylation in liver at 30 mg/kg and S6RP phosphorylation at 100 mg/kg in vivo tests.…”
Section: 3 5-triazine Derivatives Targeting Mtormentioning
confidence: 97%
See 1 more Smart Citation
“…Compound 13 ( Figure 6) was recorded as mTOR inhibitor selective over PI3K and inhibited downstream substrate Pakt of mTOR kinase up to 83% exhibiting dose-dependent inhibition [37]. This compound inhibited 18 cancer cell-lines' proliferation (IC 50 <1 μM) in tissue culture experiments, HGF-stimulated Akt phosphorylation in liver at 30 mg/kg and S6RP phosphorylation at 100 mg/kg in vivo tests.…”
Section: 3 5-triazine Derivatives Targeting Mtormentioning
confidence: 97%
“…The 4-OMe-6-aza compound 3 ( Figure 2) was displayed dramatic loss of activity against p110α, p110β, and p110δ compared with compound 2 which showed that the electron withdrawing effect being highly unfavorable to moral activity. Synthetic study on PI3K inhibitors with the triazine skeleton structure has proceeded recently [37]. = 228 ng/ml) [39].…”
Section: Pan Inhibitors Of Class I Pi3k: Zstk474 (mentioning
confidence: 99%
“…-A mixture of thiophene derivative 1 (2.53 g, 10 mmol) and phenacyl bromide (1.99 g, 10 mmol) was refl uxed in ethanol for 3 h. The solid obtained was fi ltered and crystallized from dioxane to give 14 as an orange powder. (15). -A mixture of 14 (3.71 g, 10 mmol) and malononotrile (0.66 g, 10 mmol) in ethanol (30 mL) containing sodium ethoxide (0.5 g) was refl uxed for 5 h, the reaction mixture was cooled and acidifi ed with dil.…”
Section: -{mentioning
confidence: 99%
“…Among these active compounds, thieno [3,2-d]pyrimidines have generated wide-spread interest due to their remarkable antitumor activities (3,4,14). Thus, substituted thieno [3,2-d]pyrimidines exert pronounced activity as PI3K inhibitors (GDC-0941) and EGFR and VEGFR dual inhibitors, which are used in the treatment of cancers (15)(16)(17). As a part of our continuing program on the synthesis of antimicrobial and antitumor compounds, we have earlier reported on a series of heterocyclic moieties that have biological activities (11)(12)(13).…”
mentioning
confidence: 99%
“…These include the pan-PI3K inhibitors BKM120 (Novartis), PX-886 (Oncothyreon), XL147 (SAR245408; Sanofi) and the p110a selective inhibitors BYL719, GDC0032, and INK1117 etc. [56].Because the catalytic domains of p110 and mTOR are structurally similar and mTOR activation is the downstream event of the PI3K/AKT pathway, it is expected that the dual inhibition of these targets may be more effective. Some of the dual PI3K/mTOR inhibitors currently being investigated in clinical trials include BEZ235, XL765, GDC-0980, GDC0084, SF1126, and PF-46915 etc.…”
Section: Pi3kca Inhibitorsmentioning
confidence: 99%